Awareness, Knowledge and Consumption of Postbiotics Among Students at Two Different Universities in Türkiye: A Cross-Sectional Survey - Kahve, Ayşe Nur; Yıldız, Yağmur (The European Research Journal, 2026)
Objective: Postbiotics, defined as non-viable microbial cells or their components that provide health benefits, are emerging as an important topic in functional food research. However, awareness and consumption among young adults remain limited. This study aimed to evaluate the awareness and knowledge levels of postbiotics among university students. Methods: The study population included 346 students who completed a questionnaire consisting of 17 demographic and lifestyle questions and a 20-item postbiotic knowledge scale adapted from a validated tool. Descriptive statistics were used to analyze the data. Results: It was revealed that 86.1% (n=298) of the students included in this study had never heard of postbiotics and 96.2% (n=333) had never used postbiotic supplements. Overall, 48.8% (n=169) of participants had a poor, 39.0% (n=135) a moderate, and 11.8% (n=41) a good knowledge level. Female students demonstrated significantly higher knowledge scores than males (P